Screening of stress tolerance endophytic bacteria isolated from six stress bearing plants - Somal, Manpreet Kaur; Karnwa, Arun (Journal of Postharvest Technology, 2022)
In the present study, salt tolerance and heavy metal tolerance, bacterial endophytes were isolated from six plants collected from Himachal Pradesh and Punjab states of India. Fifty isolates were obtained. The isolates were checked for their phosphate solubilization, nitrogen fixation, Urease, and Indole producing activity. Isolates were subjected to different NaCl concentrations ranging from 2% to 16% and heavy metal concentrations (lead and cadmium) 2-6%. Among 50 isolates, two isolates DL3R2 and A1S1S1 showed positive responses to phosphate solubilization, nitrogen fixation, Urease, and Indole producing activity. On comparing their ODs with control, it was found that the increase in the concentration of salt is a decrease in growth of the bacterial culture. Only two isolates R1L2 and A2L2L2 had growth at 12 ,14 and 16% NaCl concentration. However, isolates had a sharp decrease in growth with the increase in heavy metal stress. Results indicate that three isolates DL2R2, R1L2, and A1S1S1 had growth at 6% lead concentration (0.229±0.015, 0.224±0.01, 0.425±0.024), and isolates R1L2, DL3R2, and DP1L1L1 showed growth at 6% cadmium concentration. The ODs recorded at 600nm were 0.34±0.013, 0.637±0.023, 0.633±0. This study suggests that such endophytes have a scope to be used in the future to promote plant growth under salt and heavy metal stress thus promising an alternative method to make plants tolerable to different environmental stress conditions.